Using Statistical Software in Analyzing Educational Data: A Community Service to Mathematics Teacher’s in 50 Kota Regency - Nonong Amalita; Yenni Kurniawati; Dina Fitria (Pelita Eksakta, 2018)
Analyzing data using statistical software is an interesting work. Many teachers in 50 Kota regency lack of it. Given a workshop on data analysis using statistical software. There is increasing ability of teachers in analyzing data using simple statistical software. They are able to organize their data on education, i.e result of exam